Heterogenous wall thickening of gall blabber: xanthogranulomatous cholecystitis or carcinoma, with type 3 choledochal cyst. (22nd June 2012) - Darji, Parth; Thakkar, Gurudatt; Prajapati, Sanjay
Abstract : Xanthogranulomatous cholecystitis is an unusual inflammatory disease of the gallbladder characterised by severe proliferative fibrosis and the accumulation of lipid-laden macrophages in areas of destructive inflammation. Its macroscopic appearance may occasionally be confused with gallbladder carcinoma. The authors present a case of xanthogranulomatous cholecystitis with type 3 choledochal cyst in a 20-year-old man who was referred to our hospital with a 1-week history of abdominal pain and fever. He underwent endoscopic sphincterotomy and then open cholecystectomy. A histological diagnosis of xanthogranulomatous cholecystitis was made.